(untitled) (Research, Society and Development, 2022)
Objective: The objective of the present review was to relate the scientific production presented in the last 5 years on the effect of photodynamic therapy using the methylene blue photosensitizer on the microorganisms present in the oral biofilm. Methods: systematic review looking for research in English of primary studies such as randomized clinical trials and without randomization, individual case-control, and qualitative descriptive studies, using the PubMed/MEDLINE and Scopus databases as references, from 2017 to 2021. Results: 15 articles were analyzed, being 67% national publications and 33% international studies. Considering the samples described in the studies, 73% were in vitro, 7% were in vivo and 20% were clinical samples. As for the light source, 66% used laser, 20% used LED and 14% the association of laser and LED devices. The power density used ranged from 0.0026 W/cm2 to 1415 W/cm2. The energy density ranged from 3 J/cm2 to 640 J/cm2. The power ranged from 10 mW to 110 mW. The irradiation time ranged from 24 to 294 seconds. In most publications, 87% used the wavelength of 660 nm. As for the photosensitizer, the most used concentration, in 33% of the studies, was 0.01%, with the pre-irradiation time most used being 300 seconds in 40% of the studies. Conclusion: Photodynamic Methylene Blue Therapy is being accepted as effective in therapies of various oral curative conditions and has been shown to be a useful and effective therapy, as well as a complementary approach to control the development/growth of oral biofilm in clinical situations.